Atestine identities in the Iron Age Veneto, north-east Italy (9th-1st cent. BC) - Saccoccio, Fabio (2020)
The aim of this PhD thesis is to analyse identity in its broader sense (e.g. individual, gender, group, community, just to mention a few aspects), and not only as ethnic identity, by focusing on the Veneto Iron Age (9th to 1st cent. BC) archaeological record, north-east Italy, which the literature links to the Atestine culture. Prior to developing my identity argument I discuss the history of study of the Iron Age Veneto, a literature review on identity, the geography and geomorphology of the Veneto region and its settlement and socio-political pattern prior to and during the emergence period of the Atestine culture. On the basis of the literature review I have decided to approach Atestine identity in an eclectic and pragmatic way, negotiating my scientific position according to the type of question to be addressed, choosing each time the method of analysis that I believe best fits the problem to solve and not to align with a specific school of thought. I analyse selected Iron Age Atestine classes (i.e. red-and-black painted ware, Situla Art, bronze ex votos and tomb markers) following Morgan’s argument that in ancient times only particular artefacts under particular circumstances selectively carried social or political valency and Lomas’ argument that a complex hierarchy of identities and interactions between different forms of identity can be identified in Archaic Italy. The above classes were used to analyse different aspects of Atestine identity via a multi-scalar approach (i.e. inter-regional, regional and local/community levels), evaluating how the identity valency of an object may vary across time and space and, in at least one case – when objects interact at the inter-regional scale, identity acquires an ethnic valency.